Novel bio-based phosphorous-containing UV-curable flame-retardant coatings - BİRTANE, HATİCE; KAHRAMAN, MEMET VEZİR (My University, 2023)
© 2023, American Coatings Association.In this work, a novel bio-based phosphorus-containing reagent was synthesized and characterized. To obtain a flame retardant agent with acid functionality, 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and bio-based itaconic acid were first reacted. The synthesized acid then was reacted with glycidyl methacrylate to form a difunctional phosphorus-containing methacrylate flame retardant monomer. The flame retardant monomer was added to a reactive monomer matrix with a photoinitiator to prepare UV-curable coatings. The molecular structure of the flame retardant was confirmed by Fourier-transform infrared-attenuated total reflection spectroscopy and proton nuclear magnetic resonance (1H NMR) spectroscopy. The flame retardant behavior of coatings was determined using limiting oxygen index. Thermal behaviors of the films were studied by thermal gravimetric analysis. Furthermore, scanning electron microscopy/energy-dispersive spectroscopy was used to determine the elemental composition and to observe the morphology of the coatings. The properties (water adsorption, gel content, etc.) of the coatings were also studied. It was found that the addition of DOPO resulted in a significant improvement in the flame retardant and thermal properties of the coatings.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Fizikokimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Physical Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; MÜHENDİSLİK, KİMYASAL; KİMYA, FİZİKSEL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; CHEMISTRY; ENGINEERING, CHEMICAL; CHEMISTRY, PHYSICAL; Genel Kimya; Fizik Bilimleri; Yüzeyler ve Arayüzler; Yüzeyler, Kaplamalar ve Filmler; Kolloid ve Yüzey Kimyası; General Chemistry; Physical Sciences; Surfaces and Interfaces; Surfaces, Coatings and Films; Colloid and Surface Chemistry; DOPO; Flame-retardant; Glycidyl methacrylate; Itaconic acid; LOI; DOPO; Flame-retardant; Glycidyl methacrylate; Itaconic acid